Epidemiology of mental health and insanity: a review of literature - Emilene Nóbrega Medeiros; Maria de Oliveira Ferreira Filha; Rodrigo Pinheiro de Toledo Vianna (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The studies epidemiologists in the area of mental health still are seen as and few used in the elaboration of politics of health, action of health incipient, planning of the investments and programs of promotion and social whitewashing for this population. This study it has as objective to make a revision of literature on the subject, tracing as beginning of the line of the time the decade of 1970, dates probable of the trajectory of the studies epidemiologists in the area of mental health, until the present moment, focusing the studies epidemiologists in the northeast region, more specifically, in the Paraíba, where the research epidemiologist starts the spoon fruits.